Pengaruh Literasi Keuangan dan Digital Marketing terhadap Kinerja UMKM yang Dimediasi oleh Financial Technology - Damayanti, Damayanti; Roni, May; Destalia, Mediya; Subagja, Ghia (Bulletin of Community Engagement, 2024)
This study aims to determine the influence of Digital Marketing and Financial Literacy through Fintech-Based Payment Gateway on the Performance of SMEs. The population in this study is SMEs in the creative industry sector in Bandar Lampung. The sample used in this study is SMEs in the culinary subsector in Bandar Lampung with a total of 102 respondents. Data collection was conducted by distributing questionnaires to SMEs in Bandar Lampung that have been using Fintech-Based Payment Gateway in financial services and using digital media for marketing activities. Data processing used descriptive statistical tests with the assistance of SmartPLS 3 software. The data analysis techniques used include Measurement Model Test, Structural Model Test, Direct Influence Test, and Indirect Influence Test. The direct test results show that Digital Marketing and Financial Literacy have a positive and significant influence on Fintech-Based Payment Gateway, while Fintech-Based Payment Gateway has a significant influence on SMEs' performance. Indirect tests also show that Digital Marketing and Financial Literacy moderated through Fintech-Based Payment Gateway have a positive and significant influence on SMEs' performance. Keywords: Financial Literacy, Digital Marketing, Financial Technology, SMEs Performance